Physical Literacy and Physical Self-Description in Youth: Cross-Sectional Insights from Supportive Academic Settings - Wulandari Putri; Burhan Hambali; Agus Gumilar (Universitas Negeri Semarang, 2026)
Adolescent is a vital stage to form a person identity and adherence to healthy lifestyle. Physical literacy and physical self-description are two significant growing determinants in youth affecting their active lifestyles later in their adulthood period. However, studies directly investigating these two variables were limited. This research aimed at examining the correlation between physical literacy and physical self-description of adolescents and the difference of physical literacy level of adolescents from supportive academic programs, including sport-related programs and health-related programs. This study employed cross-sectional study with survey method. The samples of this study were 513 students, aged 17-21 years, selected from four sport-related programs and two health-related programs. The data were collected by using PPLI questionnaire, for measuring perceived physical literacy of the samples, and PSDQ questionnaire, for measuring the sample physical self-descriptions. The data were analyzed by using Pearson Correlation to determine the correlation between perceived physical literacy and physical self-description of the samples. To decide the difference between the level of physical literacy of adolescents majoring sport-related programs and adolescents majoring health-related programs, independent t-test was administered. The result of the data analysis found that there was a significant positive correlation between physical literacy and physical self-description in adolescents. A significant difference was also found on the level of physical literacy between students majoring sport-related program and students majoring health-related programs. This study implies that it is important to enhance physical literacy of adolescents and to maintain positive perceptions on their physical descriptions as these two variables would highly contribute to their physical activity level later in their adulthood period.